1963
DOI: 10.1093/jee/56.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Antimetabolite, Imidazole as a Pesticide1

Abstract: Irnidazole, an antimetabolite of histamine and nicotinic acid, has been found to be a safe and effective pesticide and is now undergoing field tests. Developed at U.C., Los Angeles, the new material has been patented and given the trade name "lrnutex." Imidazole, when synergized with boric acid, may be employed at low levels to proof fabric satisfactorily against insect attack. When synergized with 2-Aminopyridine, along with several newer synergists, and combined with base oil, imidazole is capable of control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, and compared to the 95-kDa aphidicidal protein, which killed 80% L. hesperus at approximately 50 μg/mL showing also some (not quantified) toxic activity against Aphis glycines (Matsumura) (Hemiptera: Aphididae) [ 9 ], the novel Cry-related protein exhibited a similar performance, killing 83% of M. persicae aphids at 40 μg/mL. The steep regression line slope of Cry-related protein for M. persicae was noticeable, and was much higher than the regression line slopes of other Bt proteins, which are usually between 0 and 4 [ 23 , 24 , 25 ], indicating that small changes in protein concentrations have a dramatic effect on aphid mortality. The ricin B-like lectin domain might be involved in the toxicity of this protein against M. persicae .…”
Section: Discussionmentioning
confidence: 99%
“…However, and compared to the 95-kDa aphidicidal protein, which killed 80% L. hesperus at approximately 50 μg/mL showing also some (not quantified) toxic activity against Aphis glycines (Matsumura) (Hemiptera: Aphididae) [ 9 ], the novel Cry-related protein exhibited a similar performance, killing 83% of M. persicae aphids at 40 μg/mL. The steep regression line slope of Cry-related protein for M. persicae was noticeable, and was much higher than the regression line slopes of other Bt proteins, which are usually between 0 and 4 [ 23 , 24 , 25 ], indicating that small changes in protein concentrations have a dramatic effect on aphid mortality. The ricin B-like lectin domain might be involved in the toxicity of this protein against M. persicae .…”
Section: Discussionmentioning
confidence: 99%
“…This premise is based on work by Watt and Jennison (1960) and Collins et al (1965), who have shown that dimetridazole has an inhibitory effect against certain strains of protozoa, bacteria and fungi. Work by Pence (1963) has shown that imidazole is an antimetabolite of histamine and nicotinic acid. The mode of action of dimetridazole may be the same as for imidazole; however, this possibility has not been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The fusion protein was purified from clarified bacterial lysate by affinity chromatography on His‐Bind ® Resin (Merck KGaA, Darmstadt, Germany). Because the elution buffer of the His‐Bind ® Purification Kit contains 1 m imidazole, which is highly toxic to insects (Pence ), the protein was desalted using a PD‐10 desalting column (GE Health care, Glattbrugg, Switzerland) and was eluted in phosphate‐buffered saline (PBS). Total protein content was determined according to the method of Bradford () using bovine serum albumin (BSA) as the standard.…”
Section: Methodsmentioning
confidence: 99%